PEMBELAJARAN MENGIDENTIFIKASI KEGIATAN EKONOMI PADA SISWA SD KELAS IV DENGAN MENGGUNAKAN MODEL QUANTUM TEACHING - Elis Nurhayati (IKIP Siliwangi, 2021)
Learning model is one of strategy to improve the quality of learning . Research aims to understand the influence of learning model quantum teaching to learning identify economic activities to their students primary school class IV SDN 5 Galanggang Batujajar.In the process of learning model quantum teaching the role of requiring teachers more creative and active in will improve the motivation to study students .Teachers capable of create the conditions learning an effective and fun for students .In this research technique data collection and observation .This research use action class consisting of four meeting , in its implementation use lesson plans ( implementation plan learning ) as the concept to make learning more directed consistent with the objectives of of learning model quantum teaching .The results of the study showed learning use the model quantum teaching can increased the motivation to study students in learning identify.